Research on the Application of Information Technology in College Physical Education. Issue 3 (February 2021) - Du, Hui; Li, Yulu; Li, Bo
Abstract: The rapid development of social economy and rapid changes in the information age have made competition for talents increasingly fierce. College students generally face greater pressure from competition in their studies, life, emotions and social development. These pressures make it more necessary to popularize leisure sports among college students. Different from the relatively boring model of traditional physical education, leisure sports emphasizes encouraging students to participate in learning independently, cultivating students' initiative and interest in sports and enhancing the fun of physical exercise. In the information age, the open and shared characteristics of the network make college physical education resources break the restrictions between schools and regions. Physical education in colleges and universities should make full use of information technology to integrate university video public classes, MOOC physical education courses, physical education videos on commercial websites and network shared physical education courses into physical education. Especially when teaching students some more complicated and difficult sports items, the online public courses can be effectively used. If there is a lack of corresponding teaching resources in the network, physical education teachers can use information technology to record corresponding video courses and integrate high-quality teaching resources. The abundant teaching resources in the information age can provide college physical education with rich content and diverse forms of online and offline multi-channel learning, realizing the sharing of teaching resources.